Kiyai Muhammad Jeddawi Sang “Singa Jambi” Di Era 1960-1980-An - A. Muthalib (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
In the past, in the territory of Tahtul Yaman along the city of Jambi, Jambi Province, there was one of the Kyai Pondok who was called by the community